2004
DOI: 10.1051/0004-6361:20047171
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of giant pulses in radio pulsars

Abstract: Abstract. Induced Compton scattering of radio emission off the particles of the ultrarelativistic highly magnetized plasma of pulsar magnetosphere is considered. The scattering between the photon beams of substantially differing frequencies and orientations appears to result in photon transfer to the higher frequency. With the decreasing spectrum of pulsar radio emission, this may imply a significant amplification of the higher-frequency intensity. A detailed analysis shows that the rays of widely spaced frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 27 publications
2
42
2
Order By: Relevance
“…While there is evidence of a broadening of the pulses as they weaken in intensity, they do not appear to be as broad as standard subpulses. This finding has implications in the model derived by Petrova (2004), where a clear power-law distribution is explained, but not a weak giant population. The power-law index derived also has implications for interpreting giant pulse emission on the basis of self organised criticality (Bak et al 1987), as suggested by Cairns (2004).…”
Section: Discussionmentioning
confidence: 70%
“…While there is evidence of a broadening of the pulses as they weaken in intensity, they do not appear to be as broad as standard subpulses. This finding has implications in the model derived by Petrova (2004), where a clear power-law distribution is explained, but not a weak giant population. The power-law index derived also has implications for interpreting giant pulse emission on the basis of self organised criticality (Bak et al 1987), as suggested by Cairns (2004).…”
Section: Discussionmentioning
confidence: 70%
“…The emission mechanism for the broadband GRPs may be different from the anomalous cyclotron resonance model (Lyutikov 2007) proposed for the characteristic property of the IPGRPs above 4GHz (Hankins & Eilek 2007), for which we did not detect the signal of the counterpart at P-S bands. In the induced scattering model (Petrova 2004), the intensity variation is attributed to the fluctuation of the optical depth to the induced scattering. Petrova (2004) suggested that the intensity amplification for the Crab GRPs is more efficient at the lower frequencies, which agrees with the correlation we found.…”
Section: Emission Mechanismmentioning
confidence: 99%
“…Gil and Melikidze (2005) proposed that giant pulses are generated by means of coherent curvature radiation of charged relativistic solitons associated with sparking discharge of the inner gap potential drop above the polar cap. Petrova (2004) argued that giant pulses and their substructure can be explaining in the terms of induced Compton scattering of pulsar radio emission of the plasma particles.…”
Section: Mechanisms Of Giant Pulses Radio Emissionmentioning
confidence: 99%